Reanimating the Dark Knight: Superheroes, Animation and the Critical Reception of The Lego Batman Movie. (March 2020) - Martin, Daniel
This article explores the critical reception of The Lego Batman Movie (Chris McKay, 2017) in the context of Batman's long history of multimedia storytelling, anchored to divergent parallel narratives across numerous platforms, and the ways the film appeals to nostalgia through metatextuality. The manner in which critics championed The Lego Batman Movie and derided the earlier live-action Batman v Superman: Dawn of Justice (Zack Snyder, 2016) gave rise to a complex discourse around the cultural value of animation and the larger blockbuster superhero cycle, and discussions of morality, merchandising and commercialism. This article therefore engages with questions of animation's apparent suitability for particular kinds of child-centric narratives regarded by critics as a vital part of American popular culture.